Aligning undergraduate nursing research with the Healey and Jenkins teaching–research nexus: Evidence-informed guidelines for lecturers - Poovanesthree Padayachee; Oluwatobi Joseph Alabi (International Journal of Educational Management & Development Studies, 2026)
Undergraduate nursing research modules play a pivotal role in cultivating inquiry-driven practitioners, yet lecturers frequently encounter structural and pedagogical barriers that hinder students' readiness for postgraduate education. This study sought to create evidence-informed guidelines to enhance research lecturers' pedagogical practices within undergraduate nursing curricula, utilising the Healey and Jenkins research–teaching nexus as a guiding framework. A qualitative case study was undertaken at a public university’s nursing department in South Africa. Twelve lecturers and supervisors involved in teaching or assessing research modules were purposively selected from local and international higher education nursing institutions. Data collection involved semi-structured interviews and document reviews, followed by thematic analysis. Six themes emerged, reflecting lecturers' challenges, including limited timeframes, inadequate student engagement, deficiencies in research conceptualisation, excessive workload demands, and institutional resource limitations. Evidence based guidelines were developed and aligned with the four quadrants of the Healey and Jenkins framework (research-tutored, research-based, research-led, and research-oriented), offering actionable recommendations for advancing research pedagogy. The findings highlight the potential of embedding inquiry-based, ethically grounded, and scaffolded approaches across all undergraduate levels to bolster research competence, critical thinking, and preparedness for postgraduate study. Adoption of these guidelines can support lecturer development, curriculum enhancement, and departmental quality assurance in nursing education programmes.